A novel approach to analyze white noise ERGs in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Combining temporal white noise stimulation and silent substitution technique: wnERGs driven by single photoreceptor types in LIAIS mice - Joachimsthaler, Anneka; Stallwitz, Nina; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2021)
CRIS-Team WoS Importer:2021-09-24

Genetic disruption of bassoon in two mutant mouse lines causes divergent retinal phenotypes - Ryl, Miriam; Urbasik, Alexander; Gierke, Kaspar; Babai, Norbert; Joachimsthaler, Anneka; Feigenspan, Andreas; Frischknecht, Renato; Stallwitz, Nina; Fejtová, Anna; Kremers, Jan; von Wittgenstein, Julia; Brandstätter, Johann Helmut (The FASEB Journal, 2021)
Bassoon (BSN) is a presynaptic cytomatrix protein ubiquitously present at chemical synapses of the central nervous system, where it regulates synaptic vesicle replenishment and organizes voltage-gated Ca2+ channels. In sensory photoreceptor synapses, BSN additionally plays a decisive role in anchoring the synaptic ribbon, a presynaptic organelle and functional extension of the active zone, to the presynaptic membrane. In this study, we functionally and structurally analyzed two mutant mouse lines with a genetic disruption of Bsn-Bsngt and Bsnko -using electrophysiology and high-resolution microscopy. In both Bsn mutant mouse lines, full-length BSN was abolished, and photoreceptor synaptic function was similarly impaired, yet synapse structure was more severely affected in Bsngt/gt than in Bsnko/ko photoreceptors. The synaptic defects in Bsngt/gt retina coincide with remodeling of the outer retina-rod bipolar and horizontal cell sprouting, formation of ectopic ribbon synaptic sites-and death of cone photoreceptors, processes that did not occur in Bsnko/ko retina. An analysis of Bsngt/ko hybrid mice revealed that the divergent retinal phenotypes of Bsngt/gt and Bsnko/ko mice can be attributed to the expression of the Bsngt allele, which triggers cone photoreceptor death and neurite sprouting in the outer retina. These findings shed new light on the existing Bsn mutant mouse models and might help to understand mechanisms that drive photoreceptor death.
CRIS-Team Scopus Importer:2021-04-16
Keywords: active zone; bassoon; photoreceptor; photoreceptor death; ribbon synapse

How the use of dim red-light pre-recording affects ERG responses of mice with long-wavelength shifted opsin - Joachimsthaler, Anneka; Stallwitz, Nina; Kremers, Jan (INVESTIGATIVE OPHTHALMOLOGY & VISUAL SCIENCE, 2022)
CRIS-Team WoS Importer:2022-09-30

Luminance white noise electroretinograms (wnERGs) in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (Frontiers in neuroscience, 2022)
PurposeTo record and analyse electroretinograms (ERGs) to luminance stimuli with white noise temporal profiles in mice. White noise stimuli are expected to keep the retina in a physiologically more natural state than, e.g., flashes. The influence of mean luminance (ML) was studied. MethodsElectroretinograms to luminance temporal white noise (TWN) modulation (wnERGs) were measured. The white noise stimuli contained all frequencies up to 20 Hz with equal amplitudes and random phases. Responses were recorded at 7 MLs between -0.7 and 1.2 log cd/m(2). Impulse response functions (IRFs) were calculated by cross correlating the averaged white noise electroretinogram (wnERG) responses with the stimulus. Amplitudes and latencies of the initial trough and subsequent peak in the IRFs were measured at each ML. Fourier transforms of the IRFs resulted in modulation transfer functions (MTFs). wnERGs were averaged across different animals. They were measured twice and the responses at identical instances in the 1st and 2nd recordings were plotted against each other. The correlation coefficient (r(repr)(2)) of the linear regression quantified the reproducibility. The results of the first and second measurement were further averaged. To study the underlying ERG mechanisms, the ERG potentials at the different MLs were plotted against those at the lowest and highest ML. The correlation coefficients (r(ML)(2)) were used to quantify their similarities. ResultsThe amplitudes of the initial (a-wave-like) trough of the IRFs increased with increasing ML. The following positive (b-wave-like) peak showed a minimum at -0.4 log cd/m(2) above which there was a positive correlation between amplitude and ML. Their latencies decreased monotonously with increasing ML. In none of the IRFs, oscillatory potential (OP)-like components were observed. r(repr)(2) values were minimal at a ML of -0.1 log cd/m(2), where the MTFs changed from low-pass to band-pass. r(ML)(2) values increased and decreased with increasing ML when correlated with responses obtained at the highest or the lowest ML, respectively. ConclusionWhite noise electroretinograms can be reliably recorded in mice with luminance stimuli. IRFs resemble flash ERGs superficially, but they offer a novel procedure to study retinal physiology. New components can be described in the IRFs. The wnERGs are either rod- or cone-driven with little overlap.
CRIS-Team WoS Importer:2023-01-06

Single opsin driven white noise ERGs in mice - Stallwitz, Nina; Joachimsthaler, Anneka; Kremers, Jan (Frontiers in Neuroscience, 2023)
Purpose: Electroretinograms elicited by photopigment isolating white noise stimuli (wnERGs) in mice were measured. The dependency of rod- and cone-opsin-driven wnERGs on mean luminance was studied. Methods: Temporal white noise stimuli (containing all frequencies up to 20 Hz, equal amplitudes, random phases) that modulated either rhodopsin, S-opsin or L*-opsin, using the double silent substitution technique, were used to record wnERGs in mice expressing a human L*-opsin instead of the native murine M-opsin. Responses were recorded at 4 mean luminances (MLs). Impulse response functions (IRFs) were obtained by cross-correlating the wnERG recordings with the corresponding modulation of the photopigment excitation elicited by the stimulus. So-called modulation transfer functions (MTFs) were obtained by performing a Fourier transform on the IRFs. Potentials of two repeated wnERG recordings at corresponding time points were plotted against each other. The correlation coefficient (r2repr) of the linear regression through these data was used to quantify reproducibility. Another correlation coefficient (r2ML) was used to quantify the correlations of the wnERGs obtained at different MLs with those at the highest (for cone isolating stimuli) or lowest (for rod isolating stimuli) ML. Results: IRFs showed an initial negative (a-wave like) trough N1 and a subsequent positive (b-wave like) peak P1. No oscillatory potential-like components were observed. At 0.4 and 1.0 log cd/m2 ML robust L*- and S-opsin-driven IRFs were obtained that displayed similar latencies and dependencies on ML. L*-opsin-driven IRFs were 2.5–3 times larger than S-opsin-driven IRFs. Rhodopsin-driven IRFs were observed at −0.8 and − 0.2 log cd/m2 and decreased in amplitude with increasing ML. They displayed an additional pronounced late negativity (N2), which may be a correlate of retinal ganglion cell activity. R2repr and r2ML values increased for cones with increasing ML whereas they decreased for rods. For rhodopsin-driven MTFs at low MLs and L*-opsin-driven MTFs at high MLs amplitudes decreased with increasing frequency, with much faster decreasing amplitudes for rhodopsin. A delay was calculated from MTF phases showing larger delays for rhodopsin- vs. low delays for L*-opsin-driven responses. Conclusion: Opsin-isolating wnERGs in mice show characteristics of different retinal cell types and their connected pathways.
CRIS-Team Scopus Importer:2023-08-25
Keywords: electroretinography (ERG); mouse retina; photopigment; silent substitution; temporal white noise (TWN)